Pengaruh Pengungkapan Environment, Social, and Governance (ESG) Terhadap Nilai Perusahaan dengan Keunggulan Kompetitif sebagai Variabel Moderasi - Muhammad Chairi Farrel; Fajar Gustiawaty Dewi (Jurnal Ekonomi, Akuntansi, dan Perpajakan, 2025)
This study examines the effect of ESG disclosure on firm value and the moderating role of competitive advantage in energy sector companies listed on the Indonesia Stock Exchange during 2020–2023. Using a quantitative approach with purposive sampling and multiple linear regression analysis, the results show that ESG disclosure has a positive and significant effect on firm value. However, when competitive advantage is introduced as a moderating variable, the direct effect of ESG becomes insignificant, while the interaction between ESG disclosure and competitive advantage shows a positive and significant impact on firm value. These findings imply that ESG practices alone may not be sufficient to enhance firm value unless accompanied by a strong competitive position. The study highlights the importance of integrating ESG strategies with the company’s core competencies to maximize value creation, particularly in highly competitive industries like energy.